A fé e a razão como constitutivas da interioridade metafísica nos solilóquios, de Agostinho de Hipona - Melo, Ubirajara Vieira de (2021)
Among the many interests generated by the Soliloques, by Saint Augustine of Hippo, it is possible that the interiorizing metaphysical itinerary in search of God and the soul is not only unheard of in his works (and perhaps in the old tradition, as well), but also one of the exemplary ways of searching for faith seeking understanding. Thus, the articulation between faith and reason has taken a central place in Saint Augustine’s thoughts, who became one of its greatest representatives. In Soliloquies, one can understand how such a journey, which was the beginning of the young catechumen’s religious life, is ready to provide very solid bases by means of the liberal arts, especially the dialectics, without being apart from the authoritative gifts of faith. What is already found in Cassiciacum’s first dialogues, i.e. the dialogue between faith and reason in confrontation with skepticism, against new scholars, up to the pursuit for the happiness within the rationality found in the wisdom of faith, such as one sees in The Happy Life, in Soliloquies it gains a new and very well defined object and a very clear methodology. One investigates truths believed by faith (God and the soul), although here they are investigated by means of reason, through dialects. In Book I, the Augustinian bases for “place” and the way how reason/faith investigates are settled. As for the “place” of investigation of metaphysical realities, the answer lies in the interiority, in such a way that the objects investigated and found there – God and the soul – meet their consistency in the fact of interiority being the place for truth, which is eternal, just as are the investigated metaphysical objects. Such movement, however, would be impossible without the “how”. “How” is the doctrine/ lies in the doctrine of enlightenment, which, in Soliloquies, can only find a sketch, although this one is relevant enough to be taken into consideration – even more when it is straightly related to the articulation of faith: it is God-Truth who, indeed, enlightens the rational mind that thinks and investigates metaphysical truths, which are Saint Augustine’s main interests. The investigation of God, though, soon comes to an end, due to the lack of elements of faith missed by a catechumen Augustine. As for the soul, its deepening is made possible by the use of dialetics, as well as by the analysis of what is true and what is false in the knowing soul as a subiectum. The consequences of such an investigation for the conclusion of the immortality of the soul are Book II’s the conducting axis in Soliloquies. The result of such reading is the unmistakable demonstration of the perception of both faith and reason as constitutive parts of the metaphysical interiority (God and the soul) pursued by the Hipponese in each paragraph of the dialogue